NEW PUBLIC MANAGEMENT, ACCOUNTING REFORM, AND INSTITUTIONAL PERSPECTIVE OF PUBLIC SECTOR ACCOUNTING IN INDONESIA - ALI DJAMHURI; MAHMUDI MAHMUDI (Jurnal Bisnis dan Akuntansi, 2006)
This study discusses the development of New Public Management (NPM) and accounting reform in public sector organization. The first part of this study discusses the theoretical concept and Characteristics of NPM as well as the relevant factors behind the development of NPM around the world. The second part tries to relate accounting reform in the context of NPM. Special attention is also given to complexities emerge in the implementation of accounting reform, that is a movement from single entry and cash basis accounting into accrual based and double entry accounting systems. At the end, this study discusses the institutional perspective in sociology relevant to public sector accounting, specifically correlated to the process of accounting reform. As Indonesia now is in the process of implementing autonomy and decentralization policies which one of its initiative is putting accrual double entry accounting systems in place, this study also specifically highlight the process of accounting reform in Indonesia.